Who Put Hate in My Sunday Paper? - Omid Safi (International Institute of Islamic Thought, 2009)
Uncovering the Israeli-Republican-Evangelical Networks behind the “Obsession” DVD Something strange showed up inside the Sunday newspapers of millions of Americans last September. Thematerial included alongside comics, coupons, and advertisement for local stores is a controversial DVD called “Obsession: Radical Islam’sWar against theWest.” Some 28 million copies of it were distributed for free in this fashion. In some ways, this campaign’s scale and ideological venom were unprecedented: many newspapers stated that they had never previously distributed freeDVDs as inserts, certainly nothing with such a charged content. The copies were distributed not randomly across the country, but only in the “swing states” (viz., Florida, Pennsylvania, Ohio, Michigan, Wisconsin, Iowa, Colorado, etc.) that were seen as toss-ups in the November presidential elections between McCain and Obama. Obviously, someone was trying to influence theAmerican electorate by playing on fearmongering and hate-mongering themes. But who?Who was behind thismassive, multi-million dollar campaign? Answering that question proved harder than one might think, as the groups behind this DVD have worked hard to hide their tracks. The connections, which were partially concealed in the DVD and the distribution campaign, took one from groups in Israel to pro-Israel lobby organizations in the ...